Civil protection in earthquake risk management: Enhancing resilience and inclusivity in the City of Velika Gorica - Trut, Damir; Mihalinčić, Martina (Crisis Management Days, 2025)
The focus of this paper is on analyzing the measures, procedures, and key aspects of the civil protection system in the event of an earthquake in the City of Velika Gorica. The paper provides a thorough analysis of security standards, existing protection measures, and explores ways to improve the current system to enhance society’s resilience to natural disasters. Additionally, particular attention is given to the history of notable earthquakes, with a focus on the recent catastrophic earthquakes of 2020 and their impact on the community. The aim is to assess the development and feasibility of existing protection and rescue plans, which serve as the foundation for timely and effective responses in crisis situations. Well-developed plans reduce material damage and the number of casualties, enabling faster recovery of the community. Within the scope of protection and rescue, the paper specifically addresses the alerting system, with an emphasis on its implementation for people with disabilities and other vulnerable groups. This aspect highlights the importance of inclusivity in crisis management to ensure the safety of all citizens. The lessons learned from previous crisis events are of paramount importance for improving crisis management systems, as they allow for the extraction of positive aspects from past experiences, which aids in further refining plans and procedures. Based on these lessons, the paper proposes concrete recommendations for strengthening coordination among all stakeholders and further improving the civil protection system in future crises.